Produção de proinsulina recombinante em Pichia pastoris utilizando o promotor do gene PGK - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
According to the World Health Organization (WHO), diabetes mellitus is expected to reach 333 million by 2025 and around 2030 is going to be the second cause of death in Latin America. Therefore, an insulin production increasing becomes a need to meet future market demands. The heterologous expression system in Pichia pastoris have been increasingly used and has proven to be an attractive alternative for over expressing human genes for biotechnological purposes. Thus, this work has as main objective to produce human proinsulin by P. pastoris using a PGK gene promoter. A1 gene codes for the insulin precursor and was chemically synthesized with optimized codons for P. pastoris. This gene was cloned into expression vector / secretion under control of PGK P. pastoris promoter and integrated into the genome of P. pastoris GS115. Transformant clones were selected for increased zeocin production and from dot-blotting. The production of recombinant proinsulin was performed in YPD liquid in shake flasks at 30 ° C, 180 rpm. The supernatant was clarified by centrifugation, and detection of recombinant proteins by ELISA, electrophoresis in denaturing polyacrylamide gel, Western-blotting and finally chromatography for size exclusion. Best conditions for expression / secretion of proinsulin were established through statistical experimental design detecting the expression level by ELISA. The amount of pre-proinsulin mRNA was determined from two samples of two contrasting conditions of A140 clone with the highest and lowest production of proinsulin using Real-Time PCR (qPCR). As results, the recombinant clones that had higher resistance to Zeocin also showed more intense positive signs in the dot-blotting. Proinsulin coding sequence (A1) was efficiently expressed in P. pastoris and secreted into the cell culture supernatant, with molecular weight of approximately 7.5 kDa. The A140 clone showed significant productivity in production level within 48 to 72 hours after the improvement of the YPD culture medium showed level of 0.83 g/L of insulin expression at 72 hours, for total biomass of about 50g / L. High levels of proinsulin expression with PGK promoter using P. pastoris as host make this heterologous expression attractive for human proinsulin production as well as other industrial proteins.
Keywords: Proinsulina; Codóns otimizados; Vetor de expressão; Promotor PGK; CIÊNCIAS BIOLÓGICAS